1995
DOI: 10.1017/s0022029900030971
|View full text |Cite
|
Sign up to set email alerts
|

Microfiltration performance: physicochemical aspects of whey pretreatment

Abstract: Clarification of whey by microfiltration (MF) can be achieved after appropriate pretreatment of the feed. A control pretreatment consists of a physicochemical process comprising increased ionic calcium and pH accompanied by heat (50 °C, 15 min) to cause aggregation of complex lipid-calcium phosphate particles, which are then separated by MF. This pretreatment process was modified by increasing the temperature to 55 °C and by maintaining the pH constant during heat treatment. This modification resulted in large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Since the speed of particle cross-linking increases disproportionately with temperature, the fouling reaction at high temperatures is enhanced. For the filtration of whey and whey proteins, some authors suppose that protein crosslinking by the formation of calcium-bridges or calcium phosphate precipitation are involved in membrane fouling [12,[15][16][17][18][19]. Even though it was found that calcium had a minor effect on flux decline, calcium-based protein interactions might enhance membrane fouling at higher temperatures when calcium phosphate becomes increasingly insoluble.…”
Section: β-Lg Suspensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the speed of particle cross-linking increases disproportionately with temperature, the fouling reaction at high temperatures is enhanced. For the filtration of whey and whey proteins, some authors suppose that protein crosslinking by the formation of calcium-bridges or calcium phosphate precipitation are involved in membrane fouling [12,[15][16][17][18][19]. Even though it was found that calcium had a minor effect on flux decline, calcium-based protein interactions might enhance membrane fouling at higher temperatures when calcium phosphate becomes increasingly insoluble.…”
Section: β-Lg Suspensionsmentioning
confidence: 99%
“…Independently from processing temperature it is generally agreed that whey proteins in general and, in particular the major whey protein β-lactoglobulin (β-Lg), are the main foulants during whey filtration processes [9,[12][13][14]. In addition to whey proteins, some authors suppose that protein cross-linking by the formation of calcium-bridges or calcium phosphate precipitation are involved in membrane fouling [12,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous and recent studies (Gésan et al, 1993a(Gésan et al, , 1994) the increase of fouling versus time could be the outcome of an increasing deposit layer thickness on the membrane surface. This deposit, composed 275 mainly of calcium and phosphate aggregates could entrap protein and consequently affect their transfer to the permeate.…”
Section: Evolution Of Fouling and Transmission Versustimementioning
confidence: 86%
“…The major features were: fouling heteroqeneity connected to counter-pressure modes, static and dynamic as reported by Gésan et al (1993a); aggregates size related to pretreatment and po rosit y of the fouling deposit th us created (Gésan et al, 1994).…”
Section: Microfiltration Performancementioning
confidence: 96%
See 1 more Smart Citation